Evaluation of semen quality brought from Kundasale as replacement of locally produced semen for artificial insemination in Jaffna Peninsula, Sri Lanka - Nilani, K.; Eswaramohan, T.; Mahadhevan, P. (Faculty of Science, University of Jaffna, 2012)
Artificial Insemination (AI) with frozen semen has been proved as the most potent method for rapid genetic improvement in domestic animals. While the use of AI with fresh semen is limited by the restricted period of sperm viability, this limitation may be overcome by the storage of frozen semen. Recently AI center of Thirunelvely is being advised to use the deep-frozen semen processed from Kundasale of Central Province (CP) for AI purposes. Thus the present study was undertaken to compare the quality of locally produced stored semen (LPS) and semen brought from Kundasale in deep-frozen condition (KDFS) by assessing the viability of them as the prominent factor that determine the successful of AI service . A batch of LPS and KDFS was obtained from the AI center at Thirunelvely. LPS was diluted with 2.9% sodium citrate buffer solution to evaluate the individual progressive motility and sperm velocity, sperm morphology, and acrosome integrity. Sperm smear was prepared by using 1% eosin and 0.75% Giemsa stain to identify intact and reacted acrosome and sperm abnormalities respectively. Thawed semen was also assessed for motility examination, percentage of intact acrosome, viability and morphology. Paired‘t’ test was performed to compare the means of the viability of LPS and KDFS (P<0.05). Even though the viability and sperm velocity of KDFS (84.57 ± 0.9957%, 24.75 ± 1.887 μm/s) was lower than LPS (96.62 ± 0.7837%, 26.00 ± 1.581 μm/s), its viability is enough for successful conception rate. Therefore usage of KDFS instead of LPS won’t affect the successful rate of AI service in Jaffna Peninsula.
Keywords: Cryopreservation; Thawed semen; acrosome status